2012
DOI: 10.1111/j.1744-9987.2012.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Plasma Exchange With Dialysis in Patients With Acute Liver Failure

Abstract: Selective plasma exchange with dialysis is a blood purification therapy in which simple plasma exchange is performed using a selective membrane plasma separator while the dialysate flows out of the hollow fibers. To evaluate the effect of plasma exchange with dialysis, biochemical examination of the blood, for example, the oxidative stress regulation system and interleukin 18 levels, was performed in patients with acute liver failure. We studied four patients with acute liver failure in whom the therapy was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Selective plasma exchange (SePE) using a selective membrane separator is a modified method of simple plasma exchange (PE) . Nakae et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Selective plasma exchange (SePE) using a selective membrane separator is a modified method of simple plasma exchange (PE) . Nakae et al.…”
mentioning
confidence: 99%
“…Selective plasma exchange (SePE) using a selective membrane separator is a modified method of simple plasma exchange (PE) (1,2). Nakae et al reported that SePE with dialysis can be a useful modality for the treatment of acute liver failure (1) and drug poisoning (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selective plasma exchange has showed beneficial effects in the management of acute hepatic encephalopathy in patients with liver failure [24]. In a recent study looking at the effect of plasma exchange on four patients with ALF, a significant decrease in hepatic encephalopathy and IL-18 levels was reported with plasma exchange [25].…”
Section: Hepatic Encephalopathy In Aclfmentioning
confidence: 98%
“…PE has played a major role in rescue treatment of critically ill patients and patients with autoimmune diseases (Inoue et al, 2010;Qiu et al, 2011;Qu et al, 2011). It is especially valuable in diseases associated with liver failure because of its demonstrated irreplaceable role in clearing toxins from the liver (Nakae et al, 2012). Theoretically, PE could clear almost all toxins from the plasma, especially those that couple tightly with plasma proteins (Schutt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%